Ultrasonographic and classical risk factors of carotid atherosclerosis in patients with type–2 diabetes mellitus: Ultrazvočni in klasični dejavniki tveganja karotidne ateroskleroze pri bolnikih s sladkorno boleznijo tipa 2 - Šantl Letonja, Marija; Letonja, Mitja; Nikolajević Starčević, Jovana; Petrovič, Danijel (Acta Medico-Biotechnica, 2021)
Purpose: We determined the prevalence of the clinical and biochemical risk factors as well as the extent of atherosclerosis in carotid arteries in patients with diabetes mellitus type 2 (DMT2). Methods: A total of 289 subjects with DMT2 and 157 healthy subjects were enrolled in this prospective cross–sectional study. Levels of total cholesterol, high–density lipoprotein– cholesterol (HDL–C), low–density lipoprotein–cholesterol (LDL–C), triglycerides, fasting blood glucose, fibrinogen, and high–sensitivity C–reactive protein (hsCRP) were measured using standard biochemical methods. Carotid atherosclerosis was assessed by ultrasonography. Intima media thickness (IMT), plaque type and plaque score were also determined. Results: In comparison with healthy controls, DMT2 patients: were older and had a larger waist circumference; higher body mass index; higher prevalence of hypertension; higher values of fibrinogen, D–dimer, glucose, hsCRP, troponin and triglycerides. Patients with DMT2 had lower levels of LDL–C and they were treated more often with statins (70% vs. 5%). In comparison with healthy subjects, patients with DMT2 had an increased intima media thickness (1.09±0.12 vs. 0.98±0.14; P=0.001), higher plaque score, and more advanced types of plaques. Conclusion: In comparison with healthy subjects, patients with DMT2 had an increased carotid IMT and higher plaque burden.